“THE YAWNING HEIGHTS:” ISLAMIC HIGHER EDUCATION IN POST-SOVIET DAGHESTAN AND INTERNATIONAL EDUCATIONAL NETWORKS - NAVRUZOV, Amir (CENTRAL ASIA AND THE CAUCASUS, 2007)
The reproduction and transfer of Islamic knowledge has moved to the fore in the context of the religious upsurge at the turn of the 21st century in Daghestan and other post-Soviet Muslim regions. Religious institutions that have mosques, communities, and schools associated with them are mushrooming within a very short period, their numbers increased ten- or even hundred-fold. Back in 1988, there were only two legal Islamic educational establishments in the Soviet Union: the Mir-i ‘Arab Madrasah in Bukhara and the Islamic Institute in Tashkent. The number of registered Muslim communities (jamaats) in Daghestan increased from 27 to 599 between 1987 and 2006; there are 1,679 newly opened mosques. Scores of illegal Koranic study circles, which functioned in the private houses of alims, were replaced with 278 primary schools (maqtabs), 132 colleges (madrasahs), and 14 Islamic higher educational establishments with 43 branches at newly opened mosques.1The upsurge of Islamic education across the republic (today 40 of the 42 districts of Daghestan have Muslim schools) is arousing interest as well as panic. The press accuses the madrasahs of spreading Islamic radicalism and aggression against the non-Muslim world and calls them “schools of jihad,” a holy war by Muslims against the unfaithful; not infrequently those who talk about the “export of Islamic extremism” to the Caucasus accuse foreign anti-Russian agents.2 The abundance of quasi-academic speculations on Islamic issues notwithstanding, in Daghestan, as well as across Russia, religion, its key practices, and its institutions largely remain terra incognita. This is especially true of the Islamic education system.Little is known about the curricula, subjects, and teaching methods used by the formal and informal Islamic education system in Daghestan. We still lack reliable information about the teachers and students, the funding sources, and the careers graduates pursue. A first step in the right direction was made in 2002-2004 when an international project called Islamic Education in the Soviet Union and the Commonwealth of Independent States directed by Professor Dr. Raoul Motika of the University of Hamburg studied the Islamic and sociological aspects of the problem. As one of the participants, I gathered a wealth of sociological information about the republic’s Islamic institutions, which I am presenting here